The effect of 3D printing on the Global Value Chain: a cross-country survey - De Luca, Sofia (My University, 2016)
The past decades have been characterized by mature companies sending managers to countries where labour, engineering and management costs were lower than developed nations’. Despite the past decades, a trend inversion comes to light. This is due to critical changes in international conditions and technological improvements. In particular, 3D printing technology able to cut out retailers, intermediaries, and manufacturers of tangible goods and, therefore, to strategically reshape the Global Value Chains (GVCs). In particular, through the reunification of R&D activities with production process, 3D printing may fulfil the increasing tailor-made products demand that cannot be achieved anymore through long-offshored supply chain, resulting in reorganization of the GVC in terms of governance and location (reshoring). Thus, the investigation of the impact of 3D printing on the reshape of GVC is investigated, by taking in consideration 3D printing implementation and companies’ degree of investment in 3D printing. The data for empirical analysis was collected through an Internet-based survey. The sample firms were contacted through emails and by phone. The sample consisted of 201 international companies that perform activities at least across two countries. The results of the study indicate that 3D printing and degree of investment in the technology has always an impact on governance the GVC. Instead, as concerns relocation decision, the relationship is valid dependently on foreign sales intensity. Thereby, the firms implementing 3D printing technology tend to reshape GVC; however, the investment has to be strategic in order to gain a process innovation rather than only a product development. This research is part of the “3D printing and Global Value Chains” – cooperation project between University of Vaasa and Università di Pavia and three companies.
Keywords: 3D printing; Global Value Chains reshape; offshoring; reshoring.; fi=Taloustiede|en=Economics|; fi=Master's Degree Programme in International Business|